Efficient PAPR reduction algorithm in OFDM based on nonlinear piecewise companding - Zhitong XING; Yun LI; Deyi PENG; Bensi ZHANG; Kaiming LIU; Yuan’an LIU (Tongxin xuebao)
Focusing on the high peak-to-average power ratio （PAPR） problem in orthogonal frequency division multiplexing （OFDM） systems， a generalized hybrid of rayleigh and sine distribution based nonlinear companding algorithm for PAPR reduction in OFDM systems was provided.For the proposed algorithm， signal samples with small amplitudes remain unchanged.For the signal samples with large amplitudes， their probability density function were changed from rayleigh distribution to sine-based distribution.The proposed algorithm can effectively reduce the PAPR， and at the same time， maintain the bit error rate performance and power spectral density performance.Simulation results indicate that with the same PAPR performance， compared with referred companding schemes， the proposed algorithm has lower bit error rate and out of band radiation.